MONOLIER (MONOPOLI 5R): INNOVATION OF MONOPOLY GAMES AS 5R LEARNING MEDIA FOR EARLY EDUCATION - Fardani, Fransiska Ellisa; Ramdhani, Ahmad Tajuddin; Khasanah, Amalia Nur; Ramadhani, Bayu Aji; Ananda, Meysella; Istiqomah, Nugraheni Nur; Rinawati, Seviana (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: The understanding of 5R (Ringkas, Rapi, Resik, Rawat, and Rajin) is still low among the people. This is due to the lack of early education on the 5R concept. MONOLIER (Monopoly 5R) is an inovation of learning medium that teaches students to play and learn about 5R through monopoly games. Purpose: The purpose of this researcch was to study the effect of 5R education using games